Sistem Informasi Manajemen Aset di STMIK Bandung - Linda Apriyanti; Faiqunisa Faiqunisa; Hafizh Fauzi Ihsan (LPPM STMIK Bandung, 2024)
Asset Management Information System at STMIK Bandung (Case Study: STMIK Bandung), which is designed to build a system that can assist the Building Management Section in managing all assets at STMIK Bandung, As well as being able to assist the Building Management section in carrying out asset write-offs so that they are more accurate and efficient. The software development methodology used is the waterfall model for problems that happen in the asset processing process. The waterfall model was chosen because of the stages in it. For now, this method of asset management is effective because it can make the process of procuring assets easier for the section of building management and can assist building management in making decisions for asset disposal.